Bacterial Biosynthesis of Gold Nanoparticles Using Salmonella enterica subsp. enterica serovar Typhi Isolated from Blood and Stool Specimens of Patients - Mortazavi, Seyed Mojtabi (2017)
Salmonella is one of the most common causes of gastroenteritis. In this study, a PCR assay was developed for the rapid detection of microbial cultures of Salmonella enterica sub species of enterica serovar Typhi in samples of patients suspected typhoid. The assay was based on duplicate the STY4669-hypothetical protein gene. The gene primers were designed and blast. Then the bacteria strains were employed for the green synthesis of gold nanoparticles (AuNPs), and one of the strains represented ability to extracellular synthesis of gold nanoparticles. The nanoparticles were characterized using UV–visible spectrophotometer, X-ray powder diffraction, Transmission electron microscopy. The synthesized nanoparticles had a maximum absorption in UV–vis spectra at 556 nm, a crystalline structure, and an average size of 42 nm.